A Systematic Review of the Integration of Motivational and Behavioural Theories in Game-Based Health Interventions - Mustafa A.S.; Ali N.; Dhillon J.S. (Springer Science and Business Media Deutschland GmbH, 2023)
Behavioral research; Behaviour changes; Behavioural changes; Health interventions; Integrated models; Long-term effects; Self-determination theories; Systematic Review; Theory of planned behaviour; Health care